The Influence of Acupuncture Therapy and Dry Cupping Therapy on Decreasing Knee Pain Scale in Jabung Village, Gantiwarno, Klaten - Erlina Sekar Jati Kusuma; Estuningsih; Sri Yatmihatun (HAKTI : Indonesian Acupuncture Therapists Association, 2024)
Knee pain is a musculoskeletal disorder characterized by degenerative joint disease due to damage to the joint cartilage and bone spur growth. This condition causes knee joints to feel painful, swollen, and stiff. Acupuncture therapy and cupping therapy can alleviate knee pain complaints through stimulation at acupuncture points. Acupuncture therapy can provide analgesic effects to reduce pain, and dry cupping therapy can relax muscle tension and improve blood flow, thus reducing pain. By reducing pain, it is expected to provide comfort for knee pain sufferers.This study used a pre-experimental design with a two-group pretest-posttest design. The study was conducted from October 2021 to April 2022 in Jabung Village, Jabung Wetan Hamlet, Gantiwarno, Klaten. The study involved a sample of 32 subjects who met the inclusion and exclusion criteria, divided into 2 groups: acupuncture therapy and dry cupping therapy. The Mann-Whitney test result was 0.049, which means ρ < 0.05, indicating that H0 is rejected and Ha is accepted, indicating an influence of acupuncture therapy and dry cupping therapy on reducing knee pain scale in Jabung Village, Gantiwarno, Klaten. The mean rank of knee pain scale reduction for acupuncture therapy was 19.59 and for dry cupping therapy was 13.41, indicating that acupuncture therapy has a greater effect on reducing knee pain scale.There is an influence of acupuncture therapy and dry cupping therapy on reducing knee pain scale in Jabung Village, Gantiwarno, Klaten, but acupuncture therapy has a greater effect on reducing knee pain scale.